2021
DOI: 10.1108/ijoem-05-2020-0474
|View full text |Cite
|
Sign up to set email alerts
|

Websites' hue-context congruence as a vector of trust and behavioral intentions

Abstract: PurposeThis paper aims to determine the effect of the congruence between a website's background color and its context (product category) on online trust and resulting behavioral intentions in emerging markets.Design/methodology/approachAn online experiment, conducted on 240 web-surfers, compared two versions of a website (high vs low color-context congruence) in terms of online trust and resulting behavioral intentions. The authors also studied the moderating role of the online shopping experience on the color… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 74 publications
1
4
0
Order By: Relevance
“…Moreover, a study by Shukla et al (2022) shows relationships between website aesthetics, such as ease of navigation, and interactive and friendly visual with the purchase intention. In addition, the inability of customers to touch physical products through online shopping has led them to have more concerned about website structure, such as design, color, and size of some different products (Chen et al, 2019;Ehsani & Hosseini, 2021;Khrouf & Frikha, 2021). This is in line with the previous study by Bhatnagar et al (2019), a consumer with poor navigational ability has a lower purchase probability as they need to spend more time searching on the website.…”
Section: Website Designsupporting
confidence: 62%
“…Moreover, a study by Shukla et al (2022) shows relationships between website aesthetics, such as ease of navigation, and interactive and friendly visual with the purchase intention. In addition, the inability of customers to touch physical products through online shopping has led them to have more concerned about website structure, such as design, color, and size of some different products (Chen et al, 2019;Ehsani & Hosseini, 2021;Khrouf & Frikha, 2021). This is in line with the previous study by Bhatnagar et al (2019), a consumer with poor navigational ability has a lower purchase probability as they need to spend more time searching on the website.…”
Section: Website Designsupporting
confidence: 62%
“…On the specific example (of a hotel) they used in their research, Khrouf and Frikha came up with results indicating that the blue colour suited the content better than the red. This also contributed to a higher level of trust among users, which was previously found to be one of the main factors for making a purchase and leaving personal information on a website (Khrouf & Frikha, 2021). Lee and Rao (2010) conducted similar research.…”
Section: Introductionmentioning
confidence: 72%
“…Along with the material and shape of the product, colour is one of the most important factors taken into consideration when designing packaging (Vladić et al, 2015) which should be taken into consideration since it is expected that photographs or 3D models of different product packaging are accented on the webpages. Khrouf and Frikha (2021) found that upon first encountering a web page, the users' attention is primarily attracted by aesthetic elements such as colour. Then the user evaluates the extent to which the used colours match commercial web pages with a similar theme that he has already used.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, Ok and Min [16] analyzed the color difference, color image, and hue perception of different groups of people, finding that there was no unified color or unified image among different cultural communities. In addition to cultural differences, Lilia [17] pointed out that the background color has a relationship with people's sense of trust, and color influences people's psychology. Ruse [18] argues that whether people are attracted to web pages is determined very quickly, pointing out that color combinations may be critical to successful website design.…”
Section: Introductionmentioning
confidence: 99%